KEBUTUHAN KENDARAAN ANGKUTAN TANDAN BUAH SEGAR KELAPA SAWIT DI PT. TRITUNGGAL SENTRA BUANA - Vinky Kristian; Rossy Mirasari; Roby (JURNAL AGRIMENT, 2021)
This research is motivated by the need to ensure the availability of Fresh Fruit Bunches (FFB) in a timely manner and in fresh condition, if must be supported by the availability of other resources such as labor, harvesting equipment and tranportation vehicles. The purpose of this study was compre the needs and realization of the number of vehicles transporting FFB PT. Tritunggal Sentra Buana.The method used in this research is a field survey. Field survey conducted to collect data related to field conditions. This research data uses primary data and secondary data. Primary data in the from of calibration from and the result of the calculation of the need for FFB units and secondary, data in the form of production data and FFB transportation data.The availability of FFB transporting vehicles has met the needs of earch afdeling having 3 units of vehicles. The number of unit needed per day for branch 1 and departement 2 is2 units per day. At PT. Tritunggal Sentra Buana has 19 units of FFB transporting vehicles, each of which smoothness of the FFB transportation process is road conditions and road maintenance. At PT. Tritunggal Sentra Buana routinely carries out road maintenance such as hardening the nets that the unit passes throught and pruning the fronds.